Spatiotemporal Synergistic Effect and Categorized Management Policy of CO2 and Air Pollutant Reduction and Economic Growth Under China’s Interregional Trade - Luzhen Bai; Long Dong; Qian Li; Zhiguang Qu; Fei Li (Systems)
In this study, we utilized multi-regional input–output (MRIO) tables from 2012 to 2017 to determine the spatiotemporal characteristics of CO2 emissions, air pollutant emissions, and value added associated with trade in different regions and industries, as well as the level of coupling coordination among them. Secondly, structural decomposition analysis (SDA) was used to identify the drivers of changes in the above indicators at the regional level. The results show that consumption-based emissions exceeded those based on production in developed regions such as Jing-Jin and the eastern coastal regions, while the opposite occurred in energy hubs such as the northern coastal and central regions; the results of the value added show higher levels in production areas than in consumption areas in the eastern coastal regions, while the opposite trend was observed in the northwestern regions. In different industries, energy production and heavy manufacturing contributed significantly to CO2, PM2.5, and SO2 emissions, while the service industry contributed more to NOx and VOC emissions and value added. The relationships among the changes in the three consumption-based indicators were divided into four categories: positive synergies, negative synergies, trade-offs A, and trade-offs B. Recommendations for targeted collaborative management strategies were delineated based on a regional resource-driven classification.